2022
DOI: 10.52965/001c.37830
|View full text |Cite
|
Sign up to set email alerts
|

Indications, management, and outcomes of humeral avulsions of the glenohumeral ligament: a systematic review

Abstract: Purpose To provide an updated overview of recent literature regarding the clinical indications, management, and outcomes of humeral avulsions of the glenohumeral ligament (HAGL) lesion. Methods Medline, Cochrane and Embase were systematically searched using keywords “humeral avulsion of the glenohumeral ligament” and others to identify studies reporting on management of HAGL lesions. Studies were double-screened and reviewed by two blinded authors according to selection criteria. Data was systematically extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…HAGL, although frequently overlooked, emerges as a significant pathology that can be the underlying cause of failed Bankart repair. 9 , 10 , 11 , 12 , 13 , 14 The inferior glenohumeral ligament (IGHL) serves as the primary restraint for the glenohumeral joint in the abduction and external rotation positions, with injury to the anterior band of IGHL identified in 93% of HAGL cases. 13 , 14 While clinical diagnosis is seldom supported by imaging revealing various soft tissue and bone defects, underdiagnosis prevails due to concomitant injuries.…”
mentioning
confidence: 99%
“…HAGL, although frequently overlooked, emerges as a significant pathology that can be the underlying cause of failed Bankart repair. 9 , 10 , 11 , 12 , 13 , 14 The inferior glenohumeral ligament (IGHL) serves as the primary restraint for the glenohumeral joint in the abduction and external rotation positions, with injury to the anterior band of IGHL identified in 93% of HAGL cases. 13 , 14 While clinical diagnosis is seldom supported by imaging revealing various soft tissue and bone defects, underdiagnosis prevails due to concomitant injuries.…”
mentioning
confidence: 99%
“…Only 2 of the 79 patients managed surgically were unable to return to their prior levels of sport. The latest systematic review by Nelson et al 12 in 2022 reported 117 surgically managed HAGL lesions, of which 60 were open procedures. Of these 60 cases, only 2 studies 6 , 15 comprising 32 patients reported clinical outcomes.…”
mentioning
confidence: 99%